Computer Vision Based Pothole Detection and Notification - Punithavathy, K.; Vallikannu, R.; Swaminathan, Niveditha (International Journal of Engineering and Technology, 2018)
Potholes on the road cause accidents and lead to traffic congestion. If left unresolved, the damage worsens and time taken to fix it also increases. We aim to develop an automated pothole detection and alert system which can detect potholes and also its location. In this paper, we propose a prototype for a computer vision based pothole detection system. Blob detection is used where the potholes are Â Â Â assumed to be a blob. The potholes are determined by the algorithm that is embedded in the Pi, which captures live images using the Pi camera. The OpenCV library is utilized for accomplishing the detection. Â